Produced Water Treatment Planning Using Corrugated Plate Interceptor and Ultra Filtration for Water Recycling - Novena Lany Pangestu; Nurulbaiti Listyendah Zahra; Ariyanti Sarwono; I Wayan Koko Suryawan (Fakultas Teknik, 2021)
Produced water generated by the oil and gas industry, when treated properly, will produce water that is ready to be reused, such as for watering plants. This planning is done by treating the produced water with Corrugated Plate Interceptor (CPI) and Ultra Filtration units. This research aims to analyze the design details needed in the recycling of produced water with CPI and Ultra Filtration units. After determining the design criteria used, the dimensions for each unit are obtained. Data was collected using secondary data directly from the study site and quantitative method was used for data analysis. The land area for one CPI unit requires 55 m2 with a volume of 110 m3. The Reynolds number and Froude number for CPI units meet the design criteria with 419.8 and 0.24, respectively. The ultra-filtration unit was selected with a Flux specification of 0.15 m3/m2.hour with an operational duration of 24 hours. The results of processing with the CPI unit can at least produce oil and fat effluent of 0.038 mg/L, with the threshold for water quality is 1 mg/L. Produced water treatment planning with CPI configuration and UF membrane with storage tank requires a total land area of 63.97 m2..